Changes of Histopathological Features of Lymph Node Biopsy after Six Months (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Treatment of tubercular lymphadenitis is a crucial issue for the management of the disease.Objective: The purpose of the present study was to see the treatment outcome of tuberculous lymphadenitis patients.Methodology: This cross-sectional study was done at the Department of Pathology at Banghabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from January 2009 to March 2011 for a period of nearly two (02) years. All the patients irrespective of age and sex with the clinical features of tuberculous lymphadenitis and later confirmed by histopathological examination were selected for the study purposively. Relevant information was recorded in a prescribed data sheet and histomorphological findings were recorded accordingly. In cases where fresh specimen was available, caseous portion of lymph node was sent for culture. Fite Faraco staining was also done on lymph node sections in all cases.Results: A total number of 50 tuberculous lymphadenitis patients were recruited for this study.Conclusion: In conclusion majority of the tubercular lymphadenitis patients are presented with raised ESR with positivity of Mantoux test (MT) and well defined granuloma.Journal of National Institute of Neurosciences Bangladesh, January 2025;11(1):47-51